Functional immune responses to twelve serotypes after immunization with a 23-valent pneumococcal polysaccharide vaccine in older adults. Issue 38 (11th September 2015) - Ahn, Jong Gyun; Kim, Han Wool; Choi, Hee Jung; Lee, Jin Hwa; Kim, Kyung-Hyo
Highlights We report functional immune responses in elderly vaccinated with PPSV23. PPSV23 induced a significant increase in OPA titers to 12 serotypes in the elderly. Functional antibody activity to some serotypes was reduced with increasing age.